2013
DOI: 10.3389/fnins.2013.00100
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulation of ovarian development: programming by neonatal immune challenge

Abstract: Neonatal immune challenge by administration of lipopolysaccharide (LPS) produces enduring alterations in the development and activity of neuroendocrine, immune and other physiological systems. We have recently reported that neonatal exposure to an immune challenge by administration of LPS results in altered reproductive development in the female Wistar rat. Specifically, LPS-treated animals exhibited diminished ovarian reserve and altered reproductive lifespan. In the current study, we examined the cellular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…GO and KEGG terms involved in reproductive development and biomacromolecule biogenesis and organization were specifically detected at 0 h. Previous studies have shown that organismal LPS exposure can alter reproductive development in rat. 58 , 59 In addition, DEGs were significantly enriched in GO terms involved in biomacromolecule biogenesis in L. vannamei under nitrite stress. 17 LPS immune challenge thus may affect the reproduction and development of amphioxus.…”
Section: Discussionmentioning
confidence: 98%
“…GO and KEGG terms involved in reproductive development and biomacromolecule biogenesis and organization were specifically detected at 0 h. Previous studies have shown that organismal LPS exposure can alter reproductive development in rat. 58 , 59 In addition, DEGs were significantly enriched in GO terms involved in biomacromolecule biogenesis in L. vannamei under nitrite stress. 17 LPS immune challenge thus may affect the reproduction and development of amphioxus.…”
Section: Discussionmentioning
confidence: 98%
“…On one hand, our results suggest that the TLRs do not play a key role in this biological process. On the other hand, the widespread expression of TLRs in different developmental stages of follicles was consistent with the fact that the autoimmune system plays a critical role in the reproductive functioning in both males and females (Sominsky et al, 2013).…”
Section: Discussionmentioning
confidence: 59%
“…A recent study has shown that 2 days after in vivo neonatal LPS challenge, there is a substantial upregulation of inflammatory genes in the neonatal ovary. Specifically, the expression of TLR4 transcript, a major component of the LPS-stimulated mitogen-activated protein kinase signalling pathway, was found to be significantly increased [102]. These data indicate that peripheral administration of LPS during the perinatal period in the rat results in activation of ovarian TLR4 signalling, which may directly intervene with the formation and establishment of the finite primordial follicle pool via activation of inflammatory pathways.…”
Section: Impact Of Perinatal Lps Exposure On Reproductive Functionmentioning
confidence: 99%